Failure investigation of super heater tubes of coal fired power plant. (October 2017) - Pramanick, A.K.; Das, G.; Das, S.K.; Ghosh, M.
Graphical abstract: Highlights: Thick and thin scale formation over inside wall of tube promoted local overheating. Prolong exposure of tube material under high stress and temperature caused creep and material softening leading to reduction in wall thickness. Under high hoop stress at that elevated temperature, thinned wall material ultimately failed exhibiting 'fish mouth opening'. Abstract: Cause of failure of two adjacent super heater tubes made of Cr-Mo steel of a coal based 60 MW thermal power plant has been portrayed in present investigation. Oxide deposits were found on internal surface of tubes. Deposits created significant resistance to heat transfer and resulted in undesirable rise in component temperature. This situation, in turn, aggravated the condition of gas side that was exposed to high temperature. Localized heating coarsened carbides as well as propelled precipitation of new brittle phases along grain boundary resulting in embrittlement of tube material. Continuous exposure to high temperature softened the tube material and tube wall was thinned down with bulging toward outside. Creep void formation along grain boundary was observed and steered intergranular cracking. All these effects contributed synergistically and tubes were failed ultimately due to overload under high Hoop stress.